Pelestarian Tradisi Buka Luwur: Studi Budaya di Makam Sunan Kudus Jawa Tengah - Moh Rosyid (Universitas Negeri Medan, 2021)
This article describes and to prediction sustainability the tradition of buka luwur which is a cloth that protects the tomb of Sunan Kudus in Kauman Village, Kota District, Kudus every month Muharam/Sura. This research data were obtained by interview, participatory observation, and literature review. Data collection was analyzed using a historical approach. The tradition of open flexible has a characteristic that is the distribution of Asura porridge, nasi jangkrik, Islamic art attractions that are displayed to the public, and the replacement of old luwur with the new one. The ornaments of the luwur include jasmine, unthuk banyu, kompol, and pleats. By the committee, the old luwur was cut into pieces and distributed to residents of Kauman village and guests who attended Buka Luwur. This tradition is still preserved by the al-Aqsa Kudus Mosque caretaker and people of Kauman Village and the citizens of Kudus and surrounding areas to honor the traces of the history of islamization which was played by Sunan Kudus in the Kudus region during the times of unity.